Physical Mistreatment in Persons with Alzheimer's Disease. (14th March 2013) - VandeWeerd, Carla; Paveza, Gregory J.; Walsh, Margaret; Corvin, Jaime
Abstract : Physical mistreatment has been estimated to affect 2 million older persons each year and dramatically affects health outcomes. While researchers have attempted to examine risk factors for specific forms of abuse, many have been able to focus on only victim or perpetrator characteristics, or a limited number of psychosocial variables at any one time. Additionally, data on risk factors for subgroups such as persons with Alzheimer's disease who may have heightened and/or unique risk profiles has also been limited. This paper examines risk for physical violence in caregiver/patient dyads who participated in the Aggression and Violence in Community-Based Alzheimer's Families Grant. Data were collected via in-person interview and mailed survey and included demographics as well as measures of violence, physical and emotional health, and health behaviors. Logistic regression analysis indicated that caregivers providing care to elders with high levels of functional impairment or dementia symptoms, or who had alcohol problems, were more likely to use violence as a conflict resolution strategy, as were caregivers who were providing care to elders who used violence against them. By contrast, caregivers with high self-esteem were less likely to use violence as a conflict resolution strategy. Significant interaction effects were also noted.